2014
DOI: 10.1016/j.drudis.2014.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of inflammation: targeting GPCRs that interact with lipids and peptides

Abstract: There is a growing appreciation of the important role of resolution mediators in the successful termination of the inflammatory response. Here, we discuss the potential importance of the lipid and peptide proresolving mediators, in particular the resolvins and chemerin-derived peptides, which mediate their effects through specific G protein-coupled receptors (GPCRs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 81 publications
1
43
0
1
Order By: Relevance
“…Several key studies have established a critical role for endogenous and exogenous docosahexaenoic acid-derived lipid mediators, which appear to be share a degree of receptor commonality, 4446 in the resolution of inflammation. 7,8,47,48 Interestingly, Hsiao et al have suggested that RVD1 may increase the concentration of the anti-inflammatory cytokine, IL-10, in the lungs of smoke-exposed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several key studies have established a critical role for endogenous and exogenous docosahexaenoic acid-derived lipid mediators, which appear to be share a degree of receptor commonality, 4446 in the resolution of inflammation. 7,8,47,48 Interestingly, Hsiao et al have suggested that RVD1 may increase the concentration of the anti-inflammatory cytokine, IL-10, in the lungs of smoke-exposed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid mediators such as PGJ 2 and RvD1 exert multi ple levels of control on the inflammatory response, and mimetics based on their mode of action through G proteincoupled receptors (GPCRs) represent a tract able and very effective target for treating on going inflammation 132 . PGJ 2 was one of the first COXderived lipid mediators implicated as eliciting the resolu tion of innateimmune inflammatory responses 133 as well as regulating adaptiveimmune inflammatory responses [134][135][136] .…”
Section: Targeting Pro-resolution Pathwaysmentioning
confidence: 99%
“…It is possible that chemerin and RvE1 are interacting with the chemerin receptor in distinct ways to trigger separate downstream signalling pathways. This concept is explored in the review by Cash et al (2014). Together, these studies may reflect a direct effect of resolvins acting at their respective GPCRs on vascular smooth muscle or perhaps an indirect action mediated by inhibition of the release of thromboxane or modulation of other vasoactive mediators via resolvin GPCRs on endothelial cells.…”
Section: Discussionmentioning
confidence: 99%